Novel MEMS fully differential capacitive transducer design and analysis - Ya, Ma Li; Khan, Sheroz; Nordin, Anis Nurashikin; Al-Khateeb, Khalid A. Saeed; Islam, Md. Rafiqul; Naji, Ahmed Wathik (2011)
This paper details the design and analysis of a novel MEMS fully differential capacitive sensor which can be used to measure the parameter related to force changes, such as pressure or acceleration. This MEMS model uses a new structure to get extremely high resolution of 11.6fF/KPa. Further it has a good level of linearity as regard changes in capacitance as a function of force change.